Virtual reality for robotic laparoscopic surgical training - Fiedler, Matthew J; Chen, Shing-Jye; Judkins, Timothy N; Oleynikov, Dmitry; Stergiou, Nick (Studies in health technology and informatics, 2007)
Virtual reality (VR) simulation has been used to improve training for manual laparoscopy and to give surgeons superior performance in the operating room. However, VR has not been used to train surgeons in robotic laparoscopy. Five students of the University of Nebraska Medical Center (UNMC) and the University of Nebraska at Omaha gave consent according to UNMC ethical guidelines. Subjects performed with the Da Vinci robotic surgical system 5 trials for each of two tasks (Bimanual Carrying, BC; Needle Passing, NP). Each task was performed first in the actual robotic operating environment and then in VR. The data analysis included time to task completion, instrument tips distance traveled and the corresponding speed, and range of motion of the elbow flexion and extension of each subject. The BC and NP tasks were not significantly different between the two environments with respect to robot tip speed and the elbow range of motion for both arms. Time to task completion and distance traveled were significantly different between the two environments for both tasks. Survey results showed that subjects partially agreed that it was easy to adapt to VR and felt comfortable manipulating the robot controls in VR. They also suggested that they would like to have VR as part of their regular training. Our preliminary efforts showed promise that our VR environment is valid and it can be used for training of robotic laparoscopy. However, the differences identified need to be further explored and point to the need to further improve our VR simulation.